Miniaturization of Microwave Biosensor for Non-invasive Measurements of Materials and Biological Tissues - Hardinata, Satria; Deshours, Frédérique; Alquié, Georges; Kokabi, Hamid; Koskas, Fabien (IPTEK Journal of Proceedings Series, 2018)
Non-invasive planar complementary split ring resonators (CSRRs) coupled to microstrip line for measuring the dielectric properties of materials and biological tissues are presented in this paper. The expectations of health professionals are increasingly turning to less invasive surgical procedures and treatments. In particular, the monitoring of vital parameters (sweat, water in the lungs, etc.) or the evolution of certain pathologies, such as cancer cells, could be observed regularly if suitable devices were developed and could especially replace traditional invasive method. Appropriate miniaturized RF or microwave devices could be an alternative for some medical diagnostic applications. These devices would make it possible to determine the dielectric characteristics of biological tissues, which represent their real pathological states. It would thus be possible, by means of dielectric contrast measurements, to follow the evolution of pathology as well as the vital parameters of a patient. The objective of this research is to produce a prototype biosensor that is suitable for measurements on biological tissues and that can be miniaturized to enhance its spatial sensitivity. This work focuses on the design, electromagnetic simulations and characterization of a new miniaturized biosensors operating between 1 and 10 GHz. The ex-vivo experimental results will be shown by measuring the S-parameters of various materials and animal biological tissues. The extraction of the dielectric parameters of these samples is obtained by the measurements of materials